ENHANCING LEARNING QUALITY THROUGH PRINCIPAL SUPERVISION IN SOUTHWEST ACEH'S PUBLIC MIDDLE SCHOOLS - Nova Edison; Khairuddin; Murniati AR (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study investigates the academic supervision practices implemented by the principals of SMP Negeri 1 Manggeng and SMP Negeri 1 Setia, focusing on the essential elements of planning, execution, follow-up, and the overcoming of challenges to improve the quality of learning. Utilizing a qualitative approach, data were collected through interviews, observations, and document analysis to understand the multifaceted nature of academic supervision and its critical role in fostering educational excellence. The findings highlight the importance of collaborative planning between principals, vice principals, and teachers to establish clear supervision goals, schedules, and objectives. Such collaboration ensures that academic supervision aligns with educational goals and addresses the specific needs of teachers, significantly contributing to their preparedness and responsiveness. Effective implementation of academic supervision is identified as crucial for realizing planned objectives, employing strategies like classroom visits, observations, and individual discussions to assess and enhance teachers' instructional practices. However, challenges such as scheduling conflicts and the principals' workload highlight the need for adaptability and strategic delegation to maintain momentum in supervision activities. The study further reveals the significance of follow-up actions in translating the insights gained from supervision into tangible improvements in teaching and learning. Constructive feedback, guidance, and recognition of teachers' efforts by principals are essential in promoting a culture of continuous professional development. Addressing the challenges encountered during academic supervision necessitates flexibility, improved communication, and a commitment to providing professional development opportunities for teachers. The research concludes that academic supervision by school principals is integral to enhancing the quality of learning. Through strategic planning, effective implementation, and constructive follow-up, principals can lead their schools toward achieving higher educational standards, despite the challenges of academic supervision. This study underscores the central role of leadership in academic supervision and offers recommendations for educational policy and practice to support effective supervision processes.